Teori Konseling Kelompok: Pendekatan Dan Aplikasinya Dalam Konteks Multikultural Dan Pendidikan - Achmad Fauzi; Adjeng Nur Farida Yahya; Anastasya Restuningsih; Aunillah Ilham Syarif; Ulya Makhmudah (Departement of Mathematics Education, 2024)
Group counseling is a psychological intervention method that emphasizes group dynamics in facilitating behavior change and self-development. This research uses a qualitative approach with a literature review method. The data collected are secondary data from journals, books, as well as previous research relevant to group counseling. This article discusses the main theories in group counseling, such as reality and Adlerian theories, as well as techniques such as relaxation and cognitive restructuring. In addition, it explores the role of multicultural competence in the practice of group counseling in educational settings. Based on the literature review, group counseling has proven to be effective in increasing self-confidence, self-efficacy, and reducing negative behaviors among students. In a multicultural context, counselors' multicultural competence plays an important role in ensuring that each group member can participate equally and free from cultural discrimination. By understanding and appreciating cultural differences, group counseling in educational settings can be a powerful tool to facilitate positive behavior change and strengthen social relationships among students.